Comprehensive Analysis of the Impact of Certification on Teacher Performance and Student Learning Achievement - Mohzana; Zuana, Muhammad Mujtaba Mitra (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of certification on teacher performance through student learning achievement at Al-Furqon Educational Institution. The background of this study is driven by great attention to improving the quality of education in Indonesia, especially in terms of teacher performance that affects student learning achievement. Teacher certification implemented by the government is expected to improve teacher competence and welfare, but there is still debate about its impact on teacher performance and student achievement. Based on this, this study aims to explore more deeply the effect of certification on teacher performance and how student learning achievement can act as a mediator in the relationship. This study uses a quantitative approach with structural equation modeling (SEM) analysis. The population in this study were all teachers at Al-Furqon Educational Institution, with samples taken using census techniques, namely all teachers at the institution. The results of the study indicate that: 1) Certification has a significant effect on teacher performance, 2) Teacher performance is significantly impacted by student learning achievement. 3) Through student learning achievement as an intervening variable, certification significantly affects teacher performance. This study contributes new findings that the effect of certification on teacher performance is greater when through student learning achievement compared to the direct effect of certification. Thus, this study enriches the theory regarding the role of student learning achievement in improving teacher performance and provides practical implications for teacher certification policies that not only focus on improving teacher competence, but also pay attention to its impact on student learning achievement as an important factor in improving the quality of education as a whole.